Persistent contamination of a duodenoscope working channel in a non-clinical simulated ERCP setting - Kwakman, Judith A.; Bexkens, Michiel L.; Bruno, Marco J.; Vos, Margreet C. (Endoscopy, 2022)
Background To mitigate duodenoscope contamination, recent design enhancements have primarily focused on the distal tip. However, the working channels remain unchanged, which may be linked to biofilm formation. We assessed the persistence of microorganisms, indicative of biofilm formation, in reprocessed duodenoscopes in a non-clinical endoscopic retrograde cholangiopancreatography (ERCP) simulation setting.Methods Three new duodenoscopes were over-soiled in non-clinical ERCP simulations followed by reprocessing. After 40 tests, the Pseudomonas aeruginosa strain in the soil (Pa-type 1) was switched to a different P. aeruginosa strain (Pa-type 2) for 20 subsequent tests. Cultures of the tip and working channel were acquired after high level disinfection and overnight storage.Results One duodenoscope showed persistent growth of P. aeruginosa from the fifth test until the end of the study. Pa-type 1 remained present until the end of the study in the cultures of this duodenoscope, even after discontinuation of exposure to that specific strain. The other two duodenoscopes only showed incidental contamination. Conclusion Persistent contamination by Pa-type 1 was seen in one out of three duodenoscopes after exposure to supraphysiological levels of gut microorganisms. No clear explanation was found for this persistent contamination as exposure and handling were identical and no abnormalities of this particular duodenoscope were identified by borescope inspection.